Resenha: CAMILO, Vagner. Drummond: da Rosa do povo à Rosa das trevas. São Paulo: Ateliê Editorial, 2001. (Revista do Centro de Estudos Portugueses, 2003)
Resenha: CAMILO, Vagner. Drummond: da Rosa do povo à Rosa das trevas. São Paulo: Ateliê Editorial, 2001.